Kualitas Fisik Air, Kejadian Diare Dengan Stunting Pada Balita di Puskesmas Arso Kota - Angki Irawan; Henny Sesanti Budi Hastuty (STIKes Hang Tuah Pekanbaru, 2022)
Stunted toddlers are the result of persistent nutritional deficiencies caused by insufficient food intake, as well as infectious infections and environmental issues. The physical environment and cleanliness around the house have a significant impact on the health of the occupants, especially the nutritional status of children under the age of five. Water, sanitation, and hygiene (WASH), which includes drinking water sources, physical quality of drinking water, ownership of latrines, and hygiene, which includes the practice of washing hands, is one indirect factor that causes stunting. WASH has an impact on the nutritional health of children who are stunted, primarily due to infectious infections. The purpose of this study was to analyze the relationship between physical water quality and the incidence of diarrhea with stunting at the Arso City Health Center. The research design used cross sectional with 45 respondents as the subject. Respondents with the physical quality of water that met the requirements were 33 (73.3%) respondents, while children under five who had a history of diarrhea were 30 (66.7%) respondents. There was no relationship between physical water quality and stunting (p=0.496). There is a relationship between the incidence of diarrhea with stunting (p = 0.007).It is expected that parents who have toddlers use clean water and maintain hygiene so that their toddlers do not suffer from diarrhea.